Regression testing using orthogonal defect classification in a quality assurance environment. (1st January 2011) - Soluade, Oredola
In an environment where software development is expanding in scope, it is necessary to develop new techniques that can be used to identify defects in a product, while at the same time keeping the cost of product certification to a minimum. For the initial deployment of any software, there is no way to get around performing a complete test of the product. However, subsequent iterations of software development require complete testing of the new features, and regression-testing of the existing features using orthogonal defect classification. Random sampling techniques may also be used; but unless they are properly designed, run the risk of not being adequately representative of the whole array of test cases. Using orthogonal arrays, we can break the test cases down into categories, thereby reducing the amount of testing without sacrificing the quality of the deliverables.